Komunikasi Terapeutik di Yamet Child Development Center Sukabumi: Study Kasus Mengenai Komunikasi Terapeutik Terapis dengan Anak Berkebutuhan Khusus Eks Learning difficulties dalam Mengembangkan Potensi Keterampilan Sosial - Yanti Lestari Pujiastuti; Sastra Cahya Nugraha; Sanusi (Jurnalika : Jurnal Ilmu Komunikasi, 2022)
Therapeutic communication is a communication process in the health sector carried out by nurses, midwives, doctors, psychiatrists, and psychologists. This communication pattern is a process to create a relationship between medical personnel and patients to find out and recognize the information needs of the patient so that it can then be directed to action plans and medical actions. This communication method is a process to create a relationship between medical personnel and patients to find out and recognize the information needs of the patient so that it can then be directed to action plans and medical actions. This study aims to determine the implementation of therapeutic communication between therapists and Children with Special Needs Ex Learning difficulties in developing potential social skills at the Yamet Child Development Center Sukabumi; what are the factors that hinder therapeutic communication between therapists and Children with Special Needs Ex Learning difficulties ; and efforts that must be made in overcoming barriers to therapeutic communication for therapists in Children with Special Needs Ex Learning difficulties . The research method is qualitative with a case study approach. While the data sampling is done purposively and snowball, triangulation collection techniques, data analysis is inductive/qualitative. The results of the research on therapeutic communication between therapists and CSN ex Ld in developing the potential for social skills are going well, as can be seen from the response of children who are increasingly responsive to the direction and guidance of the therapist. The decreasing number of inhibiting factors in the implementation of therapeutic communication carried out by therapists for CSN ex Ld can be seen from the response of children who are increasingly starting to understand the guidance taught by the therapist. An increase in the effect of communication by the therapist on CSN ex Ld can be seen from how the ability and responsiveness of children increases in performing social skills.